A fast LED calibration method under near field lighting based on photometric stereo. (December 2021) - Ma, Long; Liu, Yuzhe; Liu, Jirui; Guo, Shengwei; Pei, Xin; Sun, Fengming; Fang, Shaobo
Highlights: A Novel photometric stereo based calibration method for near field LED lighting that can calibrate the position of LED simultaneously with a single camera snapshot. The mathematical analysis on light propagation between LED and camera intensity. A cost function and an iteration method that can fit the LED position and orientation accurately. Abstract: We proposed and experimentally demonstrate a calibration method to estimate the position and the orientation of the anisotropic near point LED light source from a single view. In this work, a Lambertian sphere is used as the calibration target, where the reflection model of the Lambertian sphere under the illumination of LED with given radiant intensity distribution is analyzed theoretically to establish the relationship between the recorded image intensity and the observed surface. Based on this relationship, the geometrical principle of the calibration is researched and an iteration method is presented to calculate the LED position and orientation with a cost function through minimizing the estimation error. The accuracy of the proposed method is verified by simulations with the mean estimation error lower than 5.8mm and 1.7deg for near field lighting. The experiments are performed by measuring the plaster models using the presented system, which proves the effectiveness of the proposed calibration approach.